NETWORK SECURITY: A SURVEY OF MODERN APPROACHES - Zafar, M. F.; Naheed, F.; Ahmad, Z.; Anwar, M. M. (The Nucleus, 2020)
Security is an essential element of information technology (IT) infrastructure and applications. Concerns about security of networks and information systems have been growing alongwith the rapid increase in the number of network users and the value of their transactions. The hasty security threats have driven the development of security products known as Intrusion Detection Systems (IDS) and Intrusion Prevention Systems (IPS) to detect and protect the network, server and desktop infrastructure ahead of the threat. Authentication and signing techniques are used to prevent integrity threats. Users, devices, and applications should always be authenticated and authorized before they are allowed to access networking resources. Though a lot of information is available on the internet about IDS and IPS but it all is spread on so many sites and one has to spend a considerable part of his precious time to search it. In this regard a thorough survey has been conducted to facilitate and assist the researchers. The issues and defend challenges in fighting with cyber attacks have been discussed. A comparison of the categories of network security technologies has been presented. In this paper an effort has been made to gather the scattered information and present it at one place. This survey will provide best available uptodate advancement in the area. A brief description of open source IPS has also been presented.